KONTRIBUSI KESEIMBANGAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN TENDANGAN SAMPING ATLET PENCAK SILAT TAPAK SUCI KOTA BEKASI - Candra, Juli; Natas Pasaribu, Ahmad Muclisin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to reveal the contribution of balance and leg muscle power to the side kick ability of Pencak Silat athletes at the Tapak Suci College in Bekasi. This research is included in the correlational research. The population in this study were all Tapak Suci athletes in Bekasi City, aged 15-17 years, amounting to 38 people and the sample was determined by purposive sampling technique as many as 29 male athletes alone. To get the research data used a balance test (stork stand test), leg muscle explosive power (vertical jump) and side kick ability tests. The data obtained were analyzed with produck moment and to see the correlation used dolittle double method and to know the contribution results determined by the dolittle formula. From the results of the study it can be seen that the correlation coefficient r count> r table (research hypothesis is accepted) and significant testing of the correlation coefficient of variables X1 - Y, X2 - Y and X1, X2 against Y is obtained Fcount> Ftable. From the results of this study prove: (1) there is a significant contribution between balance (X1) to the side kick capability of 23%. (2) There is a significant contribution between the leg muscle explosive power (X2) to the side kick capability of 74%. (3) There is a joint contribution of balance (X1) and leg muscle power (X2) to side kick capability (Y) of 97%.